2019
DOI: 10.1111/hiv.12782
|View full text |Cite
|
Sign up to set email alerts
|

Persistence rate of cervical human papillomavirus infections and abnormal cytology in Rwanda

Abstract: Objectives In this study, we determined the incidence and persistence of human papillomavirus (HPV) strains and of squamous intraepithelial lesions (SIL) or worse cytology in 237 HIV‐positive and HIV‐negative Rwandan women and whether the interleukin (IL)‐28B single nucleotide polymorphism (SNP) at rs12979860 correlated with susceptibility to and persistence of HPV infection. Methods Cervical samples were collected at baseline and after 9, 18 and 24 months for a 40‐HPV DNA screening test and a ThinPrep Pap tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 44 publications
(58 reference statements)
4
14
0
Order By: Relevance
“…For HR-HPV, the OR was 4.49 (95% CI 2.26–8.91) for persistent detection. Some differences between this study and the study by Adebamowo et al include a different HPV detection system (the SPF/LIPA system in the study by Adebamowo et al vs the Roche Linear Array in this study), a shorter follow-up time in the study by Adebamowo et al (6 vs 24 months), and a lack of ART data for the HIV-infected cohort in the study by Adebamowo et al Mukanyangezi et al 48 studied HPV detection in 100 HIV-uninfected and 137 HIV-infected women living in Rwanda over a 24-month period. Persistent HR-HPV but not LR-HPV occurred more often among HIV-infected women than in HIV-uninfected women.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…For HR-HPV, the OR was 4.49 (95% CI 2.26–8.91) for persistent detection. Some differences between this study and the study by Adebamowo et al include a different HPV detection system (the SPF/LIPA system in the study by Adebamowo et al vs the Roche Linear Array in this study), a shorter follow-up time in the study by Adebamowo et al (6 vs 24 months), and a lack of ART data for the HIV-infected cohort in the study by Adebamowo et al Mukanyangezi et al 48 studied HPV detection in 100 HIV-uninfected and 137 HIV-infected women living in Rwanda over a 24-month period. Persistent HR-HPV but not LR-HPV occurred more often among HIV-infected women than in HIV-uninfected women.…”
Section: Discussionmentioning
confidence: 69%
“…For HR-HPV, the OR was 4.49 (95% CI 2.26-8.91) for persistent detection. Some differences between this study and the study by Adebamowo 48 studied HPV detection in 100 HIVuninfected and 137 HIV-infected women living in Rwanda over a 24-month period. Persistent HR-HPV but not LR-HPV occurred more often among HIV-infected women than in HIV-uninfected women.…”
Section: Discussionmentioning
confidence: 82%
“…WLHIV with hrHPV are, however, at an increased risk of rapid progression to cervical disease. 2 , 3 , 4 , 5 More robust epidemiological data in WLHIV are required to clearly define this risk according to hrHPV type with longer follow-up periods, in order to inform and optimise cervical screening programmes in WLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…High-risk human papillomavirus co-infection with HIV is associated with decreased clearance, increased HPV persistence and progression to precancerous lesions and cervical cancer. 2 , 3 , 4 , 5 Invasive cervical cancer (ICC) is the most common female malignancy in Zimbabwe and is the leading cause of female cancer-related deaths with an age-standardised mortality rate of 46 per 100 000 women per year. 6…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent report by the HPV Information Centre, the most prevalent oncogenic types among women in the East Africa are HPV 16, followed by HPV 18 and HPV 52 [4]. However, recently, mainly cross-sectional studies have reported on the diversity of HPV types within and across countries, affecting the efficacy of HPV vaccinations, e.g., the diversity of prevalent HPV types in Ethiopia [5]. Other risk factors that have been associated with cervical cancer include HIV/AIDS, family history, lifestyle, and oral contraceptive use [6,7].…”
Section: Burden Of Cervical Cancer In East African Countriesmentioning
confidence: 99%